A Review of the Antimalarial, Antitrypanosomal, and Antileishmanial Activities of Natural Compounds Isolated From Nigerian Flora - Ungogo, Marzuq A.; Ebiloma, Godwin U.; Ichoron, Nahandoo; Igoli, John O.; de Koning, Harry P.; Balogun, Emmanuel O. (Frontiers in Chemistry, 2020)
The West African country Nigeria features highly diverse vegetation and climatic conditions that range from rain forest bordering the Atlantic Ocean in the South to the Desert (Sahara) at the Northern extreme. Based on data from the World Conservation Monitoring Centre of the United Nations Environmental Protection, Nigeria, with approximately 5,000 documented vascular plants, ranks amongst the top 50 countries in terms of biodiversity. Such a rich biodiversity implies that the country is rich in diverse secondary metabolites - natural products/unique chemicals produced by the plant kingdom to confer selective advantages to them. Like many tropical countries, Nigeria is also endemic to numerous infectious diseases particularly those caused by parasitic pathogens. These phytochemicals have been exploited for the treatment of diseases and as a result, a new branch of chemistry, natural product chemistry, has evolved, to try to reproduce and improve the therapeutic qualities of particular phytochemicals. In this review, we have compiled a compendium of natural products, isolated from Nigerian flora, that have been reported to be effective against certain protozoan parasites with the aim that it will stimulate interests for further investigations, and give impetus to the development of the natural products into registered drugs. In total 93 structurally characterized natural compounds have been identified with various levels of anti-parasite activity mainly from Nigerian plants. The synthesis protocol and molecular target for some of these natural anti-parasite agents have been established. For instance, the anti-plasmodial compound fagaronine (7), a benzophenanthridine alkaloid from Fagara zanthoxyloides has been successfully synthesized in the laboratory, and the anti-trypanosomal compound azaanthraquinone (55) elicits its effect by inhibiting mitochondrial electron transfer in trypanosomes. This review also discusses the barriers to developing approved drugs from phytochemicals, and the steps that should be taken in order to accelerate the development of new antiparasitics from the highlighted compounds.